2020
DOI: 10.1111/dth.14252
|View full text |Cite
|
Sign up to set email alerts
|

Serum zinc levels and efficacy of zinc treatment in acne vulgaris: A systematic review and meta‐analysis

Abstract: Oral and topical zinc have been used for the treatment of acne, but there is a lack of definitive evidence for their efficacy. (a) To determine if mean serum zinc levels differ between acne patients and controls and (b) to determine the efficacy of zinc preparations in the treatment of acne. A systematic review and meta-analysis was performed according to recommended PRISMA [Preferred Reporting Items for Systematic Reviews and Meta-Analyses] guidelines. Subjects with acne had significantly lower serum zinc lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 26 publications
1
20
0
5
Order By: Relevance
“…Oral zinc may be taken into consideration as systemic drug alone or in support to oral AB [43]. Although the exact mechanism of action remains poorly elucidated, it is believed to act directly on the microbial inflammatory equilibrium and to facilitate antibiotic absorption when used in combination.…”
Section: Systemic Treatment Of Masknementioning
confidence: 99%
“…Oral zinc may be taken into consideration as systemic drug alone or in support to oral AB [43]. Although the exact mechanism of action remains poorly elucidated, it is believed to act directly on the microbial inflammatory equilibrium and to facilitate antibiotic absorption when used in combination.…”
Section: Systemic Treatment Of Masknementioning
confidence: 99%
“…Zinc levels in the sera of patients with acne are significantly lower, and this was validated in the majority of studies identified from the last five years, 69-73 this also was confirmed by a recent review in 2020 that concluded the correlation of low serum zinc level and suggested that zinc is effective in the treatment of acne as an adjuvant or as monotherapy. 114 Three studies did not find this association, 74-76 nor did an earlier study. 115…”
Section: Discussionmentioning
confidence: 93%
“…113 Three studies did not find this association, [73][74][75] nor did an earlier study. 114 The relation between zinc and acne can be explained through its inhibitory role on tumor necrosis factor-(TNF-)α and IL-6. 115,116 Furthermore, in keratinocyte cell culture studies zinc gluconate decreased IL-8 secretion through inhibition of TLR2 and TLR4 expression, which have all proven to have a significant role in acne pathogenesis.…”
Section: Vitiligomentioning
confidence: 99%
“…Acne patients also have decreased serum zinc levels. 21 Sayyafan et al observed that erythromycin 2% with zinc acetate 1.2% as 'topical gel' and erythromycin 2% gel alone erythromycin treatment with zinc acetate was more effective than erythromycin alone with respect to reducing the number of acne lesions and severity grade of acne. 22 In a study, lactoferrin with vitamin E and zinc was more effective than placebo.…”
Section: Zinc As a Therapymentioning
confidence: 99%